1998
DOI: 10.1007/s004420050492
|View full text |Cite
|
Sign up to set email alerts
|

Sprouting success of shrubs after fire: height-dependent relationships for different strategies

Abstract: The sprouting success of co-occurring populations of shrub species in a temperate woodland of semi-arid Australia was investigated and related to population survival strategies. Straw was added to 21 × 15 m plots in the woodland, burnt and the pre-fire characteristics of shrubs were used to determine the basis for sprouting success. Species differed widely (4-94%) in sprouting success; a high percentage of established seedlings of all species were killed by fire but survival increased with height reaching a ma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
117
0
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 123 publications
(121 citation statements)
references
References 31 publications
2
117
0
2
Order By: Relevance
“…Fire usually destroys or depletes vegetation rapidly, in contrast to fire recovery that is a long-term process. Some of the plant communities in the Mediterranean ecosystems, known as resprouter species, have high elasticity after a fire because they are often able to regenerate by means of resprouting from fire resistant structures (López-Soria and Castell, 1992;Hodgkinson, 1998). Other species, the so-called obligate seeders, rely on the germination of fire protected seeds stored in the soil or in the canopy (Lloret, 1998;Arianoutsou and Ne'eman, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Fire usually destroys or depletes vegetation rapidly, in contrast to fire recovery that is a long-term process. Some of the plant communities in the Mediterranean ecosystems, known as resprouter species, have high elasticity after a fire because they are often able to regenerate by means of resprouting from fire resistant structures (López-Soria and Castell, 1992;Hodgkinson, 1998). Other species, the so-called obligate seeders, rely on the germination of fire protected seeds stored in the soil or in the canopy (Lloret, 1998;Arianoutsou and Ne'eman, 2000).…”
Section: Introductionmentioning
confidence: 99%
“…Many Mediterranean plant species exhibit the ability to recover readily after fire, either through the germination of pro-* Corresponding author: Anselm.Rodrigo@uab.es tected seeds stored in the soil seed bank or in the canopy [24], or by resprouting from aerial or subterranean fire-resistant buds [17,21,26,38]. The resprouting ability of some of the most dominant tree and shrub species in the Mediterranean Basin is well known (e.g.…”
Section: Introductionmentioning
confidence: 99%
“…Mature plants of budda (Eremophila mitchellii) also have the capacity to coppice from a lignotuberous rootstock following fire (Beeston and Webb 1977;Hodgkinson and Beeston 1995). Mature trees of this species, however, are often more vulnerable to fire (Hodgkinson 1998). At 'Mount Oxley' where budda had been decapitated at ground level by bulldozing, budda coppiced relatively freely from what appeared to be adventitious buds in the surface root system ).…”
Section: Discussionmentioning
confidence: 99%
“…More effective strategies include integration of 2 or more treatments applied sequentially at critical stages in the shrub regeneration cycle Scifres 1986). Small-plot experiments using artificial fuel have demonstrated that 2 or more fires applied annually can significantly reduce shrub populations, especially when follow-up fires are applied in the autumn (Hodgkinson 1998;Noble 2001).…”
Section: Introductionmentioning
confidence: 99%